Impact of the global commodity and financial crises on poverty in Vietnam - James Thurlow; Finn Tarp; Simon McCoy; Nguyen Manh Hai; Clemens Breisinger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Economic growth in Vietnam has been fairly resilient to the global commodity and financial crises, but it is unclear why. In addition, the impact of the crises on employment and poverty is in dispute. We develop a dynamic computable general equilibrium model to decompose impacts and estimate distributional outcomes. Our results indicate that the 2008 commodity crisis increased employment and reduced poverty by favouring labour-intensive exports, especially in agriculture. The 2009 financial crisis reversed these gains. It pushed more than a million workers into unemployment and about 3 million people below the US2-a-day poverty line, with the vast majority of these being rural dwellers. The net effect of the crises left Vietnam little changed from a baseline (no crises) path in terms of aggregate indicators including the poverty rate. An effective stimulus package has the potential to offset one third of the increase in poverty caused by the financial crisis leaving poverty rates below the (no crises) baseline.
Keywords: R0; R5; R14; R52; 330; economic crisis; growth; poverty; Vietnam